2015
DOI: 10.1371/journal.pone.0135315
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Analysis of WRKY Transcription Factors in Chinese Wild Hazel, Corylus heterophylla Fisch

Abstract: Plant WRKY transcription factors are known to regulate various biotic and abiotic stress responses. In this study we identified a total of 30 putative WRKY unigenes in a transcriptome dataset of the Chinese wild Hazel, Corylus heterophylla, a species that is noted for its cold tolerance. Thirteen full-length of these ChWRKY genes were cloned and found to encode complete protein sequences, and they were divided into three groups, based on the number of WRKY domains and the pattern of zinc finger structures. Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Evidence from genome- or transcriptome-wide analyses shows that the response of WRKYs to abiotic stresses varies according to the species. For instance, 30 putative WRKYs were identified through transcriptome analysis in Chinese wild hazel ( Corylus heterophylla Fisch ), and 23 of these WRKYs were found to be simultaneously up-regulated by cold, drought and high-salinity stresses [ 58 ]. Twenty-eight salt-responsive GarWRKYs were identified among 109 WRKY genes in a salt-tolerant wild cotton species ( Gossypium aridum ) based on transcriptome sequencing data [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from genome- or transcriptome-wide analyses shows that the response of WRKYs to abiotic stresses varies according to the species. For instance, 30 putative WRKYs were identified through transcriptome analysis in Chinese wild hazel ( Corylus heterophylla Fisch ), and 23 of these WRKYs were found to be simultaneously up-regulated by cold, drought and high-salinity stresses [ 58 ]. Twenty-eight salt-responsive GarWRKYs were identified among 109 WRKY genes in a salt-tolerant wild cotton species ( Gossypium aridum ) based on transcriptome sequencing data [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The InterPro Scan 5 analysis suggested that SiWRKY8 and SiWRKY35 are PWRKY transcription factors, which represented a subset of Group IIc probable WRKY transcription factors from plants. PWRKY transcription factors, with the InterPro number IPR017396, were known to regulate various abiotic stress responses [37]. Thus, SiWRKY8 and SiWRKY35 might regulate the biotic and abiotic stress responses.…”
Section: Conserved Motifs and Structures Of The Sesame Wrky Genesmentioning
confidence: 99%
“…6). TFs from WRKY family positively regulate salt and other environmental stress tolerance in a variety of plant species 53,54 . MADS and AP2 family TFs are also largely involved in plant abiotic stress resistance 55,56 .…”
Section: Discussionmentioning
confidence: 99%